Expert-independent classification of mature B-cell neoplasms using standardized flow cytometry: a multicentric study - Böttcher, Sebastian; Engelmann, Robby; Grigore, Georgiana; Fernandez, Paula; Caetano, Joana; Flores-Montero, Juan; van der Velden, Vincent H J; Novakova, Michaela; Philippé, Jan; Ritgen, Matthias; Burgos, Leire; Lecrevisse, Quentin; et al. (Blood advances, 2022)
Reproducible expert-independent flow-cytometric criteria for the differential diagnoses between mature B-cell neoplasms are lacking. We developed an algorithm-driven classification for these lymphomas by flow cytometry and compared it to the WHO gold standard diagnosis. Overall, 662 samples from 662 patients representing 9 disease categories were analyzed at 9 laboratories using the previously published EuroFlow 5-tube-8-color B-cell chronic lymphoproliferative disease antibody panel. Expression levels of all 26 markers from the panel were plotted by B-cell entity to construct a univariate, fully standardized diagnostic reference library. For multivariate data analysis, we subsequently used canonical correlation analysis of 176 training cases to project the multidimensional space of all 26 immunophenotypic parameters into 36 2-dimensional plots for each possible pairwise differential diagnosis. Diagnostic boundaries were fitted according to the distribution of the immunophenotypes of a given differential diagnosis. A diagnostic algorithm based on these projections was developed and subsequently validated using 486 independent cases. Negative predictive values exceeding 92.1% were observed for all disease categories except for follicular lymphoma. Particularly high positive predictive values were returned in chronic lymphocytic leukemia (99.1%), hairy cell leukemia (97.2%), follicular lymphoma (97.2%), and mantle cell lymphoma (95.4%). Burkitt and CD10+ diffuse large B-cell lymphomas were difficult to distinguish by the algorithm. A similar ambiguity was observed between marginal zone, lymphoplasmacytic, and CD10- diffuse large B-cell lymphomas. The specificity of the approach exceeded 98% for all entities. The univariate immunophenotypic library and the multivariate expert-independent diagnostic algorithm might contribute to increased reproducibility of future diagnostics in mature B-cell neoplasms.
Keywords: Immunophenotyping; Lymphoma, Large B-Cell, Diffuse; dospělí; Reproducibility of Results; folikulární lymfom; lidé; imunofenotypizace; reprodukovatelnost výsledků; Lymphoma, Follicular; Flow Cytometry; difúzní velkobuněčný B-lymfom; průtoková cytometrie; Adult; Humans